PENERAPAN FRAMEWORK CODEIGNITER DAN BOOTSTRAP PADA SISTEM PENGELOLAAN PAJAK BUMI DAN BANGUNAN DI DESA SRIDADI - Iksan Zakaria (Politeknik Negeri Indramayu, 2022)
The management of the Land and Building Tax (PBB) in Sridadi Village currently still uses a conventional system and has not been properly computerized. The current system still has obstacles, namely managers must look carefully at taxpayers who have or have not been paid off by the UNITED NATIONS, so that it takes a long time and is prone to errors. Based on this, a more efficient and well-computerized UN management system in Sridadi Village is needed. The CodeIgniter framework is a framework for creating software using PHP that is more systematic. Bootstrap is one of the CSS frameworks commonly used to make the appearance of a website more attractive. Because of the advantages offered by these two frameworks, so in this study it was proposed to apply the CodeIgniter framework combined with Bootstrap to develop the UN management system in Sridadi Village which was implemented using the SDLC waterfall method. System testing conducted using blackbox testing proves that a combination of CodeIgniter and Bootstrap frameworks can be applied to create a UN management system in Sridadi Village. CodeIgniter as a framework that organizes programs, while Bootstrap is more focused on how it looks. It is hoped that the management system created can ease the management of the UN Sridadi Village as in making a UN report in full, owed and recapitulation, as well as conducting UN payment transactions with taxpayers.